Legal Aspects of Private Vaccine Distribution and Cross-Subsidy in the National Health System - Nurhandayani, Dewi Siti; Vitrianingsih, Yeni; Issalillah, Fayola (Journal of Social Science Studies, 2024)
Vaccine distribution is an important element in the national health care system that serves to prevent disease and strengthen public health resilience. In Indonesia, private sector involvement in vaccine distribution is regulated by various laws and regulations that guarantee the public's right to health, but still require strict supervision by the state. This study aims to examine the legal aspects of vaccine distribution by the private sector and formulate how cross-subsidy mechanisms can be legally designed to guarantee access to vaccines for low-income communities. The research method used is normative legal analysis of positive legal provisions and implementing regulations in the fields of health, public financing, and consumer protection. The results of the study show that current regulations have provided a legal basis for private sector involvement in vaccine distribution, but their implementation requires refinement in the form of more detailed technical regulations. Cross-subsidies can be formulated through a tiered tariff scheme, integration with social security, and state-controlled vaccine pricing. All of these mechanisms must be complemented by a system of transparency, auditing, and legal sanctions to ensure accountability and effectiveness. This study contributes to the development of a more equitable and inclusive Indonesian health law.